2020
DOI: 10.1101/2020.09.06.274720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NLRC5 regulates expression of MHC-I and provides a target for anti-tumor immunity in transmissible cancers

Abstract: Downregulation of major histocompatibility complex I (MHC-I) on tumor cells is a primary means of immune evasion by many types of cancer. Additionally, MHC-I proteins are a primary target of humoral and cellular mechanisms associated with transplant rejection. Transmissible tumors that overcome allograft rejection mechanisms and evade anti-tumor immunity have killed thousands of wild Tasmanian devils (Sarcophilus harrisii). Interferon-gamma (IFNG) upregulates surface MHC-I expression on devil facial tumor (DFT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 96 publications
2
20
0
Order By: Relevance
“…Studies have shown that NLRC5 is a transcriptional regulator of MHC class I genes ( 66 ) and through this, activates cytotoxic CD8 + T cells as part of an anti-tumor immune response ( 67 ). The increased tumor expression of NLRC5 is associated with better outcomes in human cancer ( 68 ) and is a target of interest in anti-tumor immunity in transmissible tumors of another endangered species; the Tasmanian devil ( 69 ). Furthermore, downregulation of LGR5 in FP (log 2 FoldChange = −4.56, p adj = 1.03 × 10 −9 ) may also demonstrate evidence of an anti-tumor response through regulation of the Wnt/β-catenin signaling pathway, as increased expression of LGR5 is associated with poor prognosis in glioma ( 70 ), breast cancer ( 71 ) and oral squamous cell carcinoma ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NLRC5 is a transcriptional regulator of MHC class I genes ( 66 ) and through this, activates cytotoxic CD8 + T cells as part of an anti-tumor immune response ( 67 ). The increased tumor expression of NLRC5 is associated with better outcomes in human cancer ( 68 ) and is a target of interest in anti-tumor immunity in transmissible tumors of another endangered species; the Tasmanian devil ( 69 ). Furthermore, downregulation of LGR5 in FP (log 2 FoldChange = −4.56, p adj = 1.03 × 10 −9 ) may also demonstrate evidence of an anti-tumor response through regulation of the Wnt/β-catenin signaling pathway, as increased expression of LGR5 is associated with poor prognosis in glioma ( 70 ), breast cancer ( 71 ) and oral squamous cell carcinoma ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Natural and immunotherapy-induced tumour regressions have been observed in devils, along with antibody responses to DFT1 cells, albeit primarily in the context of MHC-I [7][8][9] . Conversely, the emerging DFT2 tumours do express MHC-I 10 , suggesting that other immune evasion mechanisms are important.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MHC-II molecules in DFT cells has not been described, although CIITA and some MHC-II transcripts can be upregulated in vitro in DFT1 cells with IFNG treatment 5 . We have previously genetically modified DFT1 and DFT2 cells that overexpress the MHC-I transactivator NLRC5 to induce stable expression of MHC-I on the cell surface 8 . The lack of MHC-II expression in DFT cells provided an opportunity to conduct similar investigations into the role of CIITA in MHC-II regulation in marsupials and transmissible cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NLRC5 is a transcriptional regulator of MHC class I genes 62 and through this, activates cytotoxic CD8 + T cells as part of an anti-tumor immune response 63 . The increased tumor expression of NLRC5 is associated with better outcomes in human cancer 64 and is a target of interest in anti-tumor immunity in transmissible tumors of another endangered species; the Tasmanian devil 65 . Furthermore, downregulation of LGR5 in FP (log2FoldChange = −4.56, padj = 1.03×10 −9 ) may also demonstrate evidence of an anti-tumor response through regulation of the Wnt/β-catenin signaling pathway, as increased expression of LGR5 is associated with poor prognosis in glioma 66 , breast cancer 67 and oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%